2008
DOI: 10.1007/s11837-008-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

The development of alumina-forming austenitic stainless steels for high-temperature structural use

Abstract: Research Summary high-temperature AlloysHow would you… …describe the overall signifi cance of this paper?Alumina-forming austenitic stainless steels hold the potential to permit signifi cantly increased operating temperatures in aggressive high-temperature oxidizing environments encountered in energy conversion and chemical process industry applications.…describe this work to a materials science and engineering professional with no experience in your technical specialty?We have discovered that creepresistant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
101
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 19 publications
3
101
0
3
Order By: Relevance
“…Creep rupture properties for select OC-4 -OC-10 alloys are shown in Table 3. Alloy OC-5 exhibited superior creep rupture life at 750°C and 100MPa, consistent with composition-creep property studies in the AFA alloys system, which have shown that optimum creep resistance occurs with Nb levels in the 1 wt.% range, although higher levels of Nb (typically in the 2-3 wt.% range are needed for optimum oxidation resistance [1,2]. At 700°C/170MPa and 650°C/250MPa, alloy OC-5 also exhibited good creep resistance.…”
Section: Technical Discussion Of Work Performed By All Partiessupporting
confidence: 79%
See 1 more Smart Citation
“…Creep rupture properties for select OC-4 -OC-10 alloys are shown in Table 3. Alloy OC-5 exhibited superior creep rupture life at 750°C and 100MPa, consistent with composition-creep property studies in the AFA alloys system, which have shown that optimum creep resistance occurs with Nb levels in the 1 wt.% range, although higher levels of Nb (typically in the 2-3 wt.% range are needed for optimum oxidation resistance [1,2]. At 700°C/170MPa and 650°C/250MPa, alloy OC-5 also exhibited good creep resistance.…”
Section: Technical Discussion Of Work Performed By All Partiessupporting
confidence: 79%
“…This behavior was superior to that observed for the baseline OC-4 alloy. The OC-5 alloy also exhibited good oxidation resistance under this aggressive test condition, despite it's lower Nb level which was optimized for creep resistance [1,2]. Figure 4 shows oxidation data for select OC AFA alloys in a simulated exhaust environment of air with 10% water vapor at 650 and 800°C.…”
Section: Technical Discussion Of Work Performed By All Partiesmentioning
confidence: 99%
“…The alumina-forming austenitic (AFA) stainless steels are a new class of hightemperature (600-900C; 1112-1652F) structural stainless steel alloy family with the potential for widespread applicability in the chemical/petrochemical process and energy production industries [1]. These steels combine the relatively low cost, excellent formability, weldability, and good high-temperature creep strength of state-of-the-art advanced austenitic stainless steels with fundamentally superior high-temperature corrosion resistance due to their ability to form protective aluminum oxide (alumina, Al 2 O 3 ) surface layers.…”
Section: Introductionmentioning
confidence: 99%
“…1), which contributes to its fundamentally superior high-temperature corrosion resistance [1]. Therefore, AFA stainless steels readily meet the DOE/ITP Program objective of seeking new thermal and degradation resistant materials with the potential to increase component lifetime by a factor of ten.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 These alloys are based on a strengthening concept similar to that of nano-scale precipitation strengthened martensitic steels; strengthened by controlling the dispersion of MC carbides and carbonitrides through additions of Nb and V. 4 HT-UPS steel development has also attempted to strength an austenitic alloy through Ti, V, Nb carbonitrides (M(C,N)) while improving the oxidation resistance by the addition of sufficient Al to result in an alloy that forms a continuous Al-rich oxide, opposed to the traditional Fe-Cr-rich oxide, at high temperature. 5 The creep-fatigue work reported herein has been conducted on a base HT-UPS alloy, which does not contain Al, and a conventional austenitic stainless steel alloy, type 316.…”
Section: Introductionmentioning
confidence: 99%